Transition of COM–COP relative phase in a dynamic balance task - Ko, Ji-Hyun; Challis, John H.; Newell, Karl M. (Human movement science, 2014)
•The COM–COP coupling generated two patterns: (1) in-phase, and (2) anti-phase.•The COM–COP pattern shows characteristics of a non-equilibrium phase transition.•The COM–COP coupling could be a collective variable of postural control system. The purpose of this study was to investigate whether the coordination between center of mass (COM) and center of pressure (COP) could be a candidate collective variable of a dynamical system that captures the organization of the multi-segmental whole body postural control system. We examined the transition of the COM–COP coordination pattern in a moving platform balance control paradigm. 10 young healthy adults stood on a moving surface of support that within a trial was sinusoidally translated in the anterior–posterior direction continuously scaling up and then down its frequency within the range from 0Hz to 3.0Hz. The COP was derived from a single force platform mounted on the moving surface of support. 4 angular joint motions (ankle, knee, hip, and neck) were measured by a 3D motion analysis system that also allowed COM to be derived. The COM–COP coordination changed from in-phase/anti-phase to anti-phase/in-phase at a certain frequency of the support surface, showed hysteresis as a function of the direction of frequency change and higher variability at the transition region. Conversely, the transition of the ankle–hip coordination consistently occurred at 0.3Hz across subjects with little between or within subject variability as a function of transition frequency and before the COM–COP transition. The findings provide evidence that: (1) the transition of the COM–COP coordination pattern is that of a non-equilibrium phase transition with critical fluctuations and hysteresis; and (2) that COM–COP coupling is a candidate collective variable of the multi-segmental whole body postural control system acting on a redundant postural task.